Effect of skipping breakfast on cardiovascular risk factors: a grade-assessed systematic review and meta-analysis of randomized controlled trials and prospective cohort studies - Yu, Junhui; Xia, Jiayue; Xu, Dengfeng; Wang, Yuanyuan; Yin, Shiyu; Lu, Yifei; Xia, Hui; Wang, Shaokang; Sun, Guiju (Frontiers in Endocrinology, 2023)
Skipping breakfast is one of the most prevalent irregular eating habits. Several pieces of evidence have reported the association between breakfast omission and a higher risk of cardiovascular diseases. Numerous publications have focused on the impact of skipping breakfast on various cardiovascular risk factors. Therefore, the current systematic review and meta-analysis aimed to assess this impact, especially with regard to anthropometric measurements, serum lipid profiles, blood pressure, and glycemic control indicators. A comprehensive search was performed in PubMed, Web of Science, Embase, Scopus, and the Cochrane Central Register of Controlled Trials up to April 1, 2023. A total of 11 eligible trials were identified to evaluate the combined effects of skipping breakfast. Final integrated results demonstrated that breakfast omission significantly decreased the body weight (mean difference = -0.66, 95% CI: -1.09 to -0.24, p = 0.002, I 2 = 0.0) and increased the level of serum low-density lipoprotein cholesterol (LDL-C) (mean difference = 9.89, 95% CI: 5.14 to 14.63, p = 0.000, I 2 = 17.3). Subgroup analysis also revealed potential factors that may affect the outcomes, for example, the physiological condition of participants, duration, gender and type of breakfast. In conclusion, skipping breakfast may reduce the body weight while it also increases the level of serum LDL-C at the same time. In view of the limited trials, further studies are needed to expound the role of breakfast omission in cardiovascular diseases.